Humanized Care from the Perception of Oncology Patients from Southern Chile - Tannia Navarrete-Correa; Flery Fonseca-Salamanca; R. Mauricio Barría (Universidad de Antioquia, 2021)
Objective. This work sought to determine the perception of behaviors of humanized nursing care and its relation with sociodemographic and clinical variables in patients hospitalized in a Hemato-Oncology Department. Methods. Analytic cross-sectional study conducted with 51 patients hospitalized in the Hemato-Oncology Unit at Hospital Base Valdivia, Chile. A survey containing sociodemographic and clinical information was applied together with the questionnaire on Perception of Behaviors of Humanized Nursing Care 3rd version" -PBHNC 3v (32 items distributed in the categories: Qualities of nursing work, Openness to nurse-patient communication, and Willingness to care). Results. Of the participants, 51% were women, with mean age of 46.5±16.6 years; 54.9% were diagnosed with Lymphoma and 78.4% were in the treatment induction stage. In 30 of the 32 items of the instrument, > 90% of the participants evaluated compliance with the behavior of caring at level of "always". By categories, it was observed that for "Willingness to care" there was significantly lower score among patients from 18 to 49 years of age (p=0.0455). For the category "Openness to nurse-patient communication" lower median score existed in patients with Myeloma (p=0.0043) and in patients in the Remission-Consolidation stage (p=0.0084). Days of hospitalization were associated significantly with the category "Willingness to care", being lower with 16 days and more (p=0.0242). Conclusion. High frequency was observed of humanized-care behaviors and small differences in their assessment that were associated with demographic factors like age, and clinical factors, like diagnosis, treatment stage, and days of hospitalization.